Fiscal policy in a currency union at the zero lower bound - David Cook; Michael B. Devereux (Asian Development Bank Institute (ADBI), 2018)
When monetary policy is constrained by the zero lower bound, fiscal policy can be used to achieve macro stabilization objectives. At the same time, fiscal policy is also a key policy variable within a single currency area that allow policy-makers to respond to regional demand asymmetries. How do these two uses of fiscal policy interact with one another? Is there an inherent conflict between the two objectives? How do the answers to these questions depend on the degree of fiscal space available to different members of the currency area? This paper constructs a two-country New Keynesian model of a currency union to address these questions. We find that the answers depend sensitively on the underlying internal structure of the currency union, notably the degree of trade openness between the members of the union.
Keywords: E2; E5; E6; 330; Liquidity trap; monetary policy; fiscal policy; international spillovers